Pengaruh Worklife Balance dan Gaya Kepemimpinan Transformasional terhadap Kepuasan Kerja dan Kinerja Karyawan - Ernawati (Journal of Economic, Management and Entrepreneurship, 2023)
PT Livia Mandiri Sejati is a company engaged in the distribution of bottled drinking water with well-known brands, namely Aqua, Mizone, Vit and Levite. This study aims to determine and explain the influence ofwork-life balance variables, transformational leadership style, job satisfaction, and employee performance. This type of research uses a comparative causal with a quantitative approach. The sample used in this study is the entire population in the company, as many as 40 employees / respondents. While the analysis technique used is the SEM test technique using the WarpPLS 7.0 application. The results of this study indicate thatWorklife Balance has a positive but insignificant effect on Job Satisfaction with a coefficient of 0.212 and a P-value of 0.075. Transformational Leadership Style has a significant positive effect on Job Satisfaction with acoefficient of 0.422 and p value of 0.001. Worklife Balance has a negative and insignificant effect on Employee Performance with a coefficient of -0.191 and p value 0.099. Transformational Leadership Style has asignificant positive effect on Employee Performance with a coefficient of 0.403 and a p value of 0.002. And Job Satisfaction has no significant positive effect on Employee Performance with a coefficient of 0.178 and p value0.116.